Tales of two planets : stories of climate change and inequality in a divided world - Freeman, John, 1974-; Andri Snær Magnason, 1973-; Roy, Anuradha (Lecturer in English); Atwood, Margaret, 1939-; Enriquez, Mariana; Groff, Lauren; Skinnebach, Lars, 1973-; Murata, Sayaka, 1979-; Sudbanthad, Pitchaya; Álvarez, Juan Miguel; Hanif, Mohammed (Penguin Books, 2020)
A follow-up to Tales of Two Americas gathers contributions from some of today's most accomplished international writers to illustrate the cause-and-effect impact of the environmental crisis on some of today's most vulnerable communities.